Pengaruh Kombinasi Biochar dan Kompos dalam Memperbaiki Kesuburan dan Pertumbuhan Tanaman Bayam - Siagian, Tengku Surya; Sepriani, Yusmaidar; Adam, Dini Hariyati; Pane, Rahmadani (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2024)
Spinach plants are a rich source of nutrients, containing various vitamins and minerals such as vitamin A, vitamin C, vitamin K, and folate. Spinach also contains iron, calcium and dietary fiber which are important for maintaining a healthy body. Spinach plants grow well in cool to warm climates and require sufficient sunlight for growth. Biochar has a wide pore structure, which allows it to absorb and store water and nutrients, helping to improve soil quality and fertility. The use of biochar from rice husks has a positive impact on agriculture and the environment. When mixed with soil, biochar can improve soil structure, reduce erosion, and increase water storage capacity. This can support better plant growth and increase agricultural land productivity. The use of compost made from cow dung also has a positive impact on the environment. By converting livestock waste into valuable compost, it reduces the potential for environmental pollution that can arise from this waste. By stimulating healthy plant growth, improving soil quality, and reducing negative impacts on the environment, the use of compost from cow manure is an important step in realizing more sustainable and productive agriculture. This research aims to investigate the effect of a combination of biochar and compost on improving Ultisol soil fertility and spinach plant growth. Providing Biochar and Compost has an effect on the growth and production of Spinach Plants (Amaranthus sp.) in this case Plant Height, Number of Leaves and Gross Plant Weight in Polybag planting media mixed with Biochar and Compost. The higher the dose of compost given, the higher the results obtained for plant height, number of leaves and gross plant weight.